Atypical radiological presentation of multiple cystic brain metastases from lung cancer simulating neurocysticercosis. Issue 10 (5th October 2019) - Barbone, Filomena; Peri, Marta; Vitale, Michela; Di Stefano, Vincenzo
Abstract : Brain metastases (BMs) are usually characterised by vasogenic oedema and mass effect, but cystic appearance can rarely occur, mimicking parasitosis, such as neurocysticercosis (NCC). A woman in her mid-50s was admitted for dizziness and upper left extremity paresis. Neuroimaging showed multiple cystic lesions consistent with multiple stages of NCC evolution, and empiric albendazole was started, without any clinical improvement. A whole-body CT revealed a pulmonary lesion in the right superior lobe. Pathological analysis from brain specimen demonstrated a clear cell lung carcinoma. The patient gradually worsened and died 4 months after the diagnosis. In conclusion, multiple cystic BMs are an atypical presentation on neuroimaging; in these cases, a meticulous diagnostic workup should be performed, looking for the possible site of malignancy. Even when it is not possible to perform a biopsy from the primitive lesion, as reported in this case, a brain biopsy should be considered.